Factors Influential on The Return of Post-Consumer Pesticide Packaging Through Reverse Logistics: A Contribution to the Establishment of Strategies - Klaumann, Paulo Vinicius; Milkievicz, Indianara Ignacio; Fagundes, Alexandre Borges; Beuren, Fernanda Hänsch; Vaz, Caroline Rodrigues; Vieira, Cleide (Revista de Gestão Social e Ambiental, 2025)
THIS IS AN ARTICLE PUBLISHED BY Revista de Gestão Social e Ambiental (e-ISSN: 1981-982X) ON 2025-03-20, AVAILABLE ONLINE: https://doi.org/10.24857/rgsa.v19n3-094 Abstract Objective: The objective of this study was to investigate variables that influence the return of pesticide packaging through reverse logistics, focusing on four key research axes: product shelf life, Effective compliance with environmental standards, Consumer behavioral issues, and Management of the reverse logistics system. Theoretical Framework: This section discusses the features of pesticide packaging, potential health risks associated with improper disposal, and factors that influence the return of this waste to the production process through reverse logistics. Method: The adopted methodology included a bibliographic survey focusing on the current state of the research object, the application of the conceptual model proposed by Marcos et al. (2025), and was complemented by Ambrozi et al. (2020) and Pokriwieski et al. (2025), followed by analyses and considerations on the Reverse Logistics System for Pesticide Packaging. Results and Discussion: From the research perspective, the variables that require more focus were consumer behavior and adequate adherence to environmental standards. Research Implications: The practical and theoretical implications of this study include a more comprehensive understanding of the various variables that can affect the return of post-consumer products via reverse logistics. Originality/Value: This study contributes to li by broadening the understanding of the variables involved in the reverse logistics of pesticide packaging. The importance and worth of this research are demonstrated by listing factors that influence the performance of reverse logistics systems, thereby offering input for the development of improvement strategies.
Keywords: Reverse Logistics; Pesticide Packaging; Influencing Factors; Campo Limpo System; InpEV